Analisis Pola Rekrutmen dan Seleksi Karyawan di BSI KCP Stabat Proklamasi - Sitohang, Misbah; Tambunan, Khairina (Medan Resource Center, 2022)
This study aims to determine the pattern of employee recruitment and selection applied at BSI KCP Stabat Proklamasi, and to find out the weaknesses of employee recruitment and selection and what obstacles occur when the recruitment and selection process is carried out at BSI KCP Stabat Proklamasi. The research method used in this study is a qualitative method with data collection techniques using interviews with Branch Managers and Branch Operational Service Managers as well as documentation. The object of the research is the BSI Stabat Proklamasi. This research is motivated by the limited sources of employee recruitment used and the distribution of job vacancies distributed through company employees and social media. So that applicants who apply do not reach the desired targer in terms of number and qualifications.